2015
DOI: 10.1007/s00438-015-1129-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of the apple (Malus domestica) HECT ubiquitin-protein ligase family and expression analysis of their responsiveness to abiotic stresses

Abstract: The ubiquitin-protein ligases (E3s) directly participate in ubiquitin (Ub) transferring to the target proteins in the ubiquitination pathway. The HECT ubiquitin-protein ligase (UPL), one type of E3s, is characterized as containing a conserved HECT domain of approximately 350 amino acids in the C terminus. Some UPLs were found to be involved in trichome development and leaf senescence in Arabidopsis. However, studies on plant UPLs, such as characteristics of the protein structure, predicted functional motifs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…Meng et al [19] analyzed 365 plant HECT genes, including 19 HECT genes from the soybean genome (2 n = 4 x = 40), and divided them into seven phylogenetic groups. Xu et al [20] identified 13 HECT genes from the apple genome (2 n = 2 x = 34) and divided them into four phylogenetic groups, consistent with those of A. thaliana .…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al [19] analyzed 365 plant HECT genes, including 19 HECT genes from the soybean genome (2 n = 4 x = 40), and divided them into seven phylogenetic groups. Xu et al [20] identified 13 HECT genes from the apple genome (2 n = 2 x = 34) and divided them into four phylogenetic groups, consistent with those of A. thaliana .…”
Section: Introductionmentioning
confidence: 99%
“…F-box proteins often mediate the mechanism of ubiquitination and degradation of stress-related proteins which may be positive or negative regulatory proteins. The F-box gene directly or indirectly affects plant hormone signal transduction pathway and affects resistance of plants to saline and alkaline conditions, especially the ABA signal pathway [ 51 , 52 ]. In this study, the expression of dehydrin DHN3 was upregulated and probable F-box protein At5g04010 was downregulated (electronic supplementary material, table S3), indicating that these two genes may be involved in the response of L. perenne roots to saline stress.…”
Section: Discussionmentioning
confidence: 99%
“…This protein complex plays an important role for unneeded protein degradation during the cell cycle. It has been found that several publications have reported that these proteins respond to salt stress [71,84,85,86,87,88,89]. Thus, it is crucial to investigate this degradation process as a pathway system in which OsFBL23 and OsFBL16 are involved.…”
Section: Discussionmentioning
confidence: 99%